Differential Substrate Usage and Metabolic Fluxes in Francisella tularensis Subspecies holarctica and Francisella novicida - Chen, Fan; Rydzewski, Kerstin; Kutzner, Erika; Häuslein, Ina; Schunder, Eva; Wang, Xinzhe; Meighen-Berger, Kevin; Grunow, Roland; Eisenreich, Wolfgang; Heuner, Klaus (Frontiers in Cellular and Infection Microbiology, 2017)
Francisella tularensis is an intracellular pathogen for many animals causing the infectious disease, tularemia. Whereas F. tularensis subsp. holarctica is highly pathogenic for humans, F. novicida is almost avirulent for humans, but virulent for mice. In order to compare metabolic fluxes between these strains, we performed 13C-labeling experiments with F. tularensis subsp. holarctica wild type (beaver isolate), F. tularensis subsp. holarctica strain LVS, or F. novicida strain U112 in complex media containing either [U-13C6]glucose, [1,2-13C2]glucose, [U-13C3]serine, or [U-13C3]glycerol. GC/MS-based isotopologue profiling of amino acids, polysaccharide-derived glucose, free fructose, amino sugars derived from the cell wall, fatty acids, 3-hydroxybutyrate, lactate, succinate and malate revealed uptake and metabolic usage of all tracers under the experimental conditions with glucose being the major carbon source for all strains under study. The labeling patterns of the F. tularensis subsp. holarctica wild type were highly similar to those of the LVS strain, but showed remarkable differences to the labeling profiles of the metabolites from the F. novicida strain. Glucose was directly used for polysaccharide and cell wall biosynthesis with higher rates in F. tularensis subsp. holarctica or metabolized, with higher rates in F. novicida, via glycolysis and the non-oxidative pentose phosphate pathway. Catabolic turnover of glucose via gluconeogenesis was also observed. In all strains, Ala was mainly synthesized from pyruvate, although no pathway from pyruvate to Ala is annotated in the genomes of F. tularensis and F. novicida. Glycerol efficiently served as a gluconeogenetic substrate in F. novicida, but only less in the F. tularensis subsp. holarctica strains. In any of the studied strains, serine did not serve as a major substrate and was not significantly used for gluconeogenesis under the experimental conditions. Rather, it was only utilized, at low rates, in downstream metabolic processes, e.g. via acetyl-CoA in the citrate cycle and for fatty acid biosynthesis, especially in the F. tularensis subsp. holarctica strains. In summary, the data reflect differential metabolite fluxes in F. tularensis subsp. holarctica and F. novicida suggesting that the different utilization of substrates could be related to host specificity and virulence of Francisella.